The top 100 most‐cited knee osteotomy publications - Matthieu Ollivier; Jean‐François Gonzalez; Axel Machado; Sachin Tapasvi; Raghbir Khakha; Ronald vanHeerwaarden; Grégoire Micicoi (Journal of Experimental Orthopaedics)
Abstract Purpose To objectively identify the 100 most influential scientific publications in knee osteotomy and provide an analysis of their main characteristics. Methods The Clarivate Analytics Web of Knowledge database was used to obtain data and metrics on knee osteotomy research. The search list was sorted by the number of citations, and articles were included or excluded based on relevance to knee osteotomy. The information extracted for each article included the author's name, publication year, country of origin, journal name, article type and the level of evidence. Results These 100 studies generated a total of 16,246 citations, with an average of 162.5 citations per article. The most‐cited article was cited 752 times. The 100 studies included in this analysis were published between 1976 and 2015. Twenty‐one different journals published these 100 publications. The majority of the publications were from the United States (n = 30), followed by Germany (n = 17) and Japan (n = 11). The most prevalent study designs were case series (n = 55) and cohort studies (n = 19). Conclusion The 100 most influential publications in knee osteotomy were cited a total of 16,246 times. The study designs most used were case series and cohort studies with low‐level evidence. This publication serves as a reference to direct orthopaedic practitioners to the 100 most influential studies in knee osteotomy and target future research directions. Clinical Relevance This analysis of the 100 most influential (or cited) scientific publications in osteotomy around the knee will provide a comprehensive inventory of the most impactful academic contributions to a field that has recently regained interest among medical students, residents, fellows and attending physicians. Level of Evidence N/A.